2011
DOI: 10.5348/ijbti-2011-5-oa-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes in random donor platelets stored for seven days in platelet additive solution

Abstract: Introduction: Platelets are small, anucleated cytoplasmic fragments that play an essential role in blood clotting and wound healing. Platelets are routinely stored in plasma for five days at 22 0 C. Aim: Our objective was to assess platelet morphology and function in random donor platelet stored for seven days in platelet additive solution. Methods: The random donor platelet was prepared by PRP method. Platelet concentrates from 50 blood donor were stored in 100% plasma (n=24) and 20:80 (n=24) additive solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…This value decreased due to sampling on Day 5, which led to a decrease in weight and, consequently, a reduction in volume. This decrease in platelet count and platelet content per final unit was consistent with other studies [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This value decreased due to sampling on Day 5, which led to a decrease in weight and, consequently, a reduction in volume. This decrease in platelet count and platelet content per final unit was consistent with other studies [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Singh et al [12] showed that the MPV and PDW remained constant until the 7th day of storage. However, Bashir et al [15] reported an increase in MPV over 10 days of storage from platelet-rich plasma (PRP) -PC and this correlated with another study by Chandra et al [11]. On the contrary, Baghdadi et al [16] reported that MPV and PDW decreased over 5…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…[ 15 ] Platelet morphology and function was found to be better preserved in additive solution on day seven as compared to platelets stored without additive solution by Chandra et al . [ 16 ]…”
mentioning
confidence: 99%